1999
DOI: 10.1021/jo990297n
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrin-Catalyzed Oxidation of 2-Cycloalkyl-3-hydroxynaphthoquinones

Abstract: Mild H2O2 oxidation of a small series of 2-cycloalkyl-3-hydroxynaphthoquinones catalyzed by 5,10,15,20-tetrakis(pentafluorophenyl)-21H,23H-porphineiron(III) chloride in methanol−dichloromethane leads in each case to the isolation of a dehydro-dimer identified as a 3-cycloalkyl-3-(2-cycloalkylnaphthoquinon-3-yl)oxy-2-oxo-2,3-dihydronaphtho-1,4-quinone and in some cases to a 2-cycloalkyl-2,3-dihydroxy-1-oxoindan-3-carboxylate. The mechanism of formation of the former is rationalized in terms of nucleophilic atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In the last two decades, oxidation of hydrocarbons catalyzed by metalloporphyrins under mild conditions has attracted much interest because of their potential application and the environmentally friendly conditions [21][22][23][24][25][26][27]. A large class of synthetic metalloporphyrins was used as catalysts for the oxidation of saturated C-H bond, C-C double bonds and aromatics [28][29][30][31][32][33][34][35]. Our group has reported that metalloporphyrins could catalyze effectively the oxidation of cyclohexane [36] and toluene [37] with air in the absence of any cocatalysts and reductant.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, oxidation of hydrocarbons catalyzed by metalloporphyrins under mild conditions has attracted much interest because of their potential application and the environmentally friendly conditions [21][22][23][24][25][26][27]. A large class of synthetic metalloporphyrins was used as catalysts for the oxidation of saturated C-H bond, C-C double bonds and aromatics [28][29][30][31][32][33][34][35]. Our group has reported that metalloporphyrins could catalyze effectively the oxidation of cyclohexane [36] and toluene [37] with air in the absence of any cocatalysts and reductant.…”
Section: Introductionmentioning
confidence: 99%
“…[10] While the corresponding Gdm rearrangement is unprecedented, the analogous Hooker oxidation rearrangement of hydroxynaphthoquinones to indane carboxylic acids served as related precedent. [11] For this study, the synthesis of the Gdm model surrogate 2-hydroxyquinone 21 (Scheme 2) commenced with aryl lithiation–alkylation of benzyl methyl ether 12 . DDQ-mediated oxidation of 13 followed by hydroxy-directed iodination provided phenol 15 .…”
mentioning
confidence: 99%
“…Stirring lawsone 1 with H 2 O 2 in MeOH/CH 2 Cl 2 (3:1) for 90 min at r.t. afforded 2,3‐dihydroxynaphthalen‐1,4‐dione ( 339 ) (Scheme ).…”
Section: Reactivity Of Lawsonementioning
confidence: 99%